2021
DOI: 10.1101/2021.12.29.474410
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deciphering sex-specific miRNAs as heat-recorders in zebrafish

Abstract: MicroRNAs (miRNAs) are important post-transcriptional regulators of gene expression in a wide variety of physiological processes, including those related to the reproductive system. Although in the last decade a plethora of miRNAs has been reported, the miRNA alterations occurred by environmental cues and their biological functions have not yet been elucidated. With the aim to identify epigenetic regulations mediated by miRNAs in the gonads in a climate change scenario, zebrafish (Danio rerio) were subjected t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 104 publications
0
1
0
Order By: Relevance
“…Chen et al, 2021;Kabirizadeh et al, 2016), suggesting a conserved role in steroid regulation. A recent study on zebrafish detected significantly more miR-499-5p in testis than in ovaries (van Gelderen et al, 2022). Yet, studies on other fish species have identified that miRNAs from the miR-499 family are involved in slow muscle phenotype determination (Duran et al, 2020) and the miR-499a-5p is key in regulating Sox6 (Sex determining region Y-box 6) activity (Nachtigall et al, 2015;X.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al, 2021;Kabirizadeh et al, 2016), suggesting a conserved role in steroid regulation. A recent study on zebrafish detected significantly more miR-499-5p in testis than in ovaries (van Gelderen et al, 2022). Yet, studies on other fish species have identified that miRNAs from the miR-499 family are involved in slow muscle phenotype determination (Duran et al, 2020) and the miR-499a-5p is key in regulating Sox6 (Sex determining region Y-box 6) activity (Nachtigall et al, 2015;X.…”
Section: Discussionmentioning
confidence: 99%